Penyelesaian Sengketa Ekonomi Syariah Pada Arbitrase - Ahmad Reza Maulana; mariani (Journal of International Multidisciplinary Research, 2023)
This research explores dispute resolution methods in the field of Sharia economics through the arbitration mechanism. With the rapid growth of Sharia-based financial industries, the need for effective dispute resolution in accordance with Sharia economic principles becomes increasingly pressing. Arbitration is considered a relevant alternative compatible with Islamic law in handling Sharia economic conflicts. This study will trace the Islamic legal principles applicable in arbitration and analyze the success and challenges of Sharia economic dispute resolution through the arbitration process. Additionally, the research will review the role of arbitration institutions and regulations supporting Sharia dispute resolution. Thus, this study provides in-depth insights into the potential of arbitration as an effective means of resolving Sharia economic disputes and its contribution to the global development of Sharia-based financial systems.